Acceptance in Telehealth of Community Health Nurses - Lindsay P. Agoilo; Bernadeth C. Abig; Caitlin D. Alonzo; Mariel Nicole M. Barcena; Dyan R. Blanco; Hussein E. Catanyag (Humanistic Network for Science and Technology (HNST), 2021)
During pandemic, telehealth is an important medium for providing patients with remote access to high-quality healthcare without increasing the risk of transmitting infections. Assessment of nurses' readiness to participate in telehealth is crucial and should begin with awareness and understanding of telehealth. The purpose of this study is to examine the factors that influence community health nurses’ decision to accept and use Telehealth. The study is a descriptive-correlational quantitative design, uses convenient and purposive sampling involving 35 community health nurses, and based on Unified Theory of Acceptance and Use of Technology model. Data analyzed by Pearson Chi-square. The study found that Performance Expectancy, Effort Expectancy, Social Influence and Facilitating Conditions were identified to be factors that affect the decision of nurses to use telehealth while Performance expectancy is found to be the greatest influence to nurses to use telehealth. Indeed, telehealth is accepted by community health nurses to be used in practice and shows positive attitude towards it. Moreover, this study draws attention to the key role of education of nurses in influencing their efficiency, ease of use, and intention to use telehealth.Keywords: telehealth; information technology; nurses